ROLE OF MODIFIED ECT IN PATIENTS WITH BODY DYSMORPHIC DISORDER WITH SUICIDAL IDEATION AND DEPRESSIVE EPISODE : A CASE REPORT - Dr Shilpa; Dr Jatin Dhaman; Dr Palak Talwar (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Body dysmorphic disorder (BDD) is a distressing condition often comorbid with major depressive disorder (MDD), posing significant challenges for treatment. While selective serotonin reuptake inhibitors (SSRIs) are commonly used, managing refractory cases remains difficult. Electroconvulsive therapy (ECT), typically effective for medication-resistant depression, has not been considered an alternative for treatment-refractory BDD. Here, we present a case of a 19-year-old woman with BDD and comorbid MDD, unresponsive to SSRIs and antipsychotic medication. After experiencing incapacitation and suicidal ideation, her symptoms appeared to resolve with ECT, with remission sustained for two months. This case highlights the potential efficacy of ECT in managing treatment-resistant depression associated with BDD and, in select cases, addressing dysmorphic symptoms as well